Between history and politics: the image of Mykhailo Hrushevsky in German Slavic studies of the first third of the 20th century - Vitalii Telvak; Viktoria Telvak; Bohdan Yanyshyn (Przegląd Nauk Historycznych, 2021)
The article is dedicated to the reception of Mykhailo Hrushevsky’s academic achievements in German science and journalism during the first third of the 20th century, in the years of World War I and the interwar period. The authors emphasize that German scientists were generally honest about the achievements and activity of the Ukrainian historian. Despite their scepticism towards M. Hrushevsky’s Anti-Normanism ideology, they followed closely the emergence of his major scientific works. In the reception of the Ukrainian historian’s work, the academic motivation definitely dominated over the political one, although the latter indirectly appeared in many statements devoted to him. The authors prove the vivid presence of Hrushevsky’s thought in the German Slavic discourse of the period.